Strategi Komunikasi Politik Caleg Perempuan dalam Pileg 2019 di Kota Malang - Umari, Firdha; Indra Dewi, Sulih (Unitri Press, 2020)
This study aimed to find out the political communication strategies of women legislative candidates and what obstacles faced by them. This study used qualitative method and to determine the informants it was wit purposive sampling. Data collection techniques were through interviews and documentation. This study interviewed four woman candidates from different political parties in Malang, and for the first joining a legislative elections. The results of the political communication stretegies were a door to door, approaching religious and structural leaders, used political consultant and had a lot of campaign team were proven to effective in Malang. The obstacles for the women in involving in politics were lack of money and political knowledge and also multiple roles as house wives and ploticians became their internal issue.